PENGARUH ASPEK-ASPEK SELF-EFFICACY TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII DI SMP NEGERI 2 BUMI RAYA - Siti Nurjanah; Hadjar, Ibnu; Bennu, Sudarman (Jurnal Elektronik Pendidikan Matematika Tadulako, 2022)
This research was conducted in class VIII at SMP Negeri 2 Bumi Raya which aims to determine (1) the influence of self-efficacy on the aspect of magnitude on students' mathematics learning outcomes; (2) the influence of self-efficacy aspects of strength on students' mathematics learning outcomes; (3) the influence of the generality aspect of self-efficacy on students' mathematics learning outcomes; (4) the influence of self-efficacy aspects of magnitude, aspects of strength and aspects of generality together on students' mathematics learning outcomes. The research population was 75 students. Sampling using a census. Data collection techniques using questionnaires and documentation. The results showed that (1) in the aspect of magnitude, a significance value of 0.00<0.05, means that there is an influence of the magnitude aspect on the mathematics learning outcomes of class VIII students at SMP Negeri 2 Bumi Raya. (2) in the aspect of strength, a significance value of 0.00<0.05, means that there is an influence of the strength aspect on the mathematics learning outcomes of class VIII students at SMP Negeri 2 Bumi Raya (3) in the generality aspect, a significance value of 0.432> 0.05, means that there is no influence of the generality aspect on the mathematics learning outcomes of class VIII students at SMP Negeri 2 Bumi Raya, and (4) Simultaneously a significance value of 0.00 <0.05, meaning that there was an influence of the aspects of magnitude, strength and generality together on the mathematics learning outcomes of class VIII students at SMP Negeri 2 Bumi Raya.